The pre-purchase condition of the lease contract between the comparative legislative texts and the practical applications in Algeria - Sidahmed, Messirdi (The International tax journal, 2025)
The rental dependence is based on a very creative idea, which is financing through leasing with the possibility of ownership at the end of the contract, but the effectiveness of the rental dependence may be reduced in light of the total reliance on the provisions of the Algerian law, which omitted the condition of buying the subject of the contract, that is, the lessor may lease one of his properties only. Thus, the Algerian legislator has missed trading opportunities for assets on the one hand, and has given those wishing to obtain financing the opportunity to choose the most appropriate money for their project on the other hand. On the other hand, it is clear from the extrapolation of the application in Algeria (the lease credit contracts of Al Baraka Bank and Natixis Algeria, for example) that the lease credit contracts settled on the inclusion of the condition of purchasing the subject of the contract by the lessor and then leasing it, on the selection and negotiation of the supplier, the selection of the asset and its receipt by the lessee, although the ownership of that asset will transfer to the lessor.